2017
DOI: 10.4142/jvs.2017.18.s1.281
|View full text |Cite
|
Sign up to set email alerts
|

Development and trial of vaccines againstBrucella

Abstract: The search for ideal brucellosis vaccines remains active today. Currently, no licensed human or canine anti-brucellosis vaccines are available. In bovines, the most successful vaccine (S19) is only used in calves, as adult vaccination results in orchitis in male, prolonged infection, and possible abortion complications in pregnant female cattle. Another widely deployed vaccine (RB51) has a low protective efficacy. An ideal vaccine should exhibit a safe profile as well as enhance protective efficacy. However, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 94 publications
0
70
0
1
Order By: Relevance
“…Here we demonstrated that the vaccine strain BoΔabcBA did not cause lesions or disease in immunized dogs, which is smilar to previous findings in mice [20] and rams [22] in which this strain also did not cause lesions. Commercial vaccines against bovine brucellosis are usually administered to young and non-pregnant females, because these vaccine strains possesses residual virulence and can cause abortion in pregnant females [37] or orchitis and epididymitis in males [41]. In contrast, BoΔabcBA did not induce any clinical change in both male and female immunized dogs.…”
Section: Plos Onementioning
confidence: 99%
“…Here we demonstrated that the vaccine strain BoΔabcBA did not cause lesions or disease in immunized dogs, which is smilar to previous findings in mice [20] and rams [22] in which this strain also did not cause lesions. Commercial vaccines against bovine brucellosis are usually administered to young and non-pregnant females, because these vaccine strains possesses residual virulence and can cause abortion in pregnant females [37] or orchitis and epididymitis in males [41]. In contrast, BoΔabcBA did not induce any clinical change in both male and female immunized dogs.…”
Section: Plos Onementioning
confidence: 99%
“…In our study, the DNA vaccine enhanced by the recombinant protein booster induced a specific humoral immune response against rVIRB9 and rVIRB12, but it offered low protection for the mice against infection. Specific antibodies are important in reducing the initial phase of a Brucella infection, but a strong humoral immunity unaccompanied by cell-mediated immunity (CMI) cannot provide total protection against the Brucella organism (Lalsiamthara and Lee, 2017). In some situations, inoculation with "naked" plasmid DNA has been shown to not produce an immune response as strong as either purified protein or even a commercial Brucella vaccine (Cassataro et al, 2007;Golshani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of live vaccines, such as S19, in controlling infections is most likely a direct effect of the capacity of the bacteria to infect the host cell, and to allow the immune system access to a variety of antigens that jointly contribute to a stronger and more extensive response. However, this vaccine induces abortions in pregnant animals and is virulent for humans; moreover, it elicits anti-Brucella antibodies that interfere with serodiagnosis (Lalsiamthara and Lee, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals infected with brucellosis show symptoms of chronic infection, which has a direct economic impact via reduced fertility, increases in abortion, reductions in weight and a substantial decline in milk production (Khan and Zahoor ). Several live vaccines have been developed and are used in certain countries, but they have not been widely adopted (Lalsiamthara and Lee ).…”
Section: Introductionmentioning
confidence: 99%